PERILAKU SEKSUAL BERISIKO INFEKSI MENULAR SEKSUAL - Lenny Irmawaty Sirait (Poltekkes Kemenkes Medan, 2021)
Sexually Transmitted Infections (STIs) are various infections that can be transmitted from one person to another through sexual contact. The spread of STIs to women and men (90%) occurs through sexual intercourse, both vaginal, anal and oral, the rest through blood products or tissue transfer that has been exposed to pathogens or can be transmitted through medical devices, as well as from mother to fetus in the womb or while birth process. This study aims to determine the relationship between sexual intercourse patterns and the incidence of sexually transmitted infections in women of reproductive age at the Makassar District Health Center, East Jakarta 2019. This research method is a type of quantitative research with a cross-sectional research design, using the inclusion and exclusion criteria for a sample of 55 people, the type of data. primer, measuring instrument questionnaire and laboratory results, analysis of chi square test data. The results showed that out of 46 women of childbearing age who had a poor pattern of sexual relations and sexually transmitted infections were 41 people (89.1%) and 5 people (10.9%) had sexually transmitted infections while 9 people had a pattern of sexual intercourse. well and sexually transmitted infections were 1 person (11.1) and sexually transmitted infections were 8 people (89.9%) pvalue = 0.01 (p <0.05). Conclusion The Relationship between Sexual Relationship Patterns and the Incidence of Sexually Transmitted Infection in Women of Fertile Age at the Makassar District Health Center 2019 (p value = 0.01)